Lessons Learned about Faith Formation in the Midst of a Pandemic - Nishioka, Rodger (Religious education, 2021)
The way faith is formed depends upon the zeitgeist, the spirit of the age. Faith formation cannot happen in a vacuum. It is shaped and informed by all that is happening. In our time, the COVID-19 pandemic is happening. In this essay I reflect on faith formation amid the zeitgeist of the Coronavirus, considering ways that the pandemic requires religious educators to seek new methods and practices for educational ministry that forms people in faith.